MATHEMATICS COMMUNICATION MISTAKES IN SOLVING HOTS PROBLEMS - Lelly Nur Rachmawati; Yus Mochamad Cholily; Zukhrufurrohmah Zukhrufurrohmah (Jurnal Infinity, 2021)
Student mistakes in communicating mathematical ideas are still widely practiced. Therefore, it is essential to analyze students' mathematical communication errors in solving mathematical problems so that learning planning can be better. This study aims to describe students' mathematics communication errors in solving higher-order thinking skills in linear algebra and matrix subject. The type of research is a qualitative descriptive study. They were 155 students as subject research. The data analysis started by collecting students' answers and then grouped them according to mathematics communication skills criteria. Later identified and analyzed the errors made by students of each mathematics communication criteria. The results showed that mathematical communication errors on the indicators of writing mathematical situations were concept errors and principle errors. The declaring idea's mathematical communication error is a concept error, a principle error, and an operation error. Furthermore, mathematical communication errors on the indicator state that solving-problem using the language itself is a concept error and operator error.